2020
DOI: 10.1002/admi.201901696
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gas Sensing Performance of Organic Field‐Effect Transistors by Modulating the Dimensions of Triethylsilylethynyl‐Anthradithiophene Microcrystal Arrays

Abstract: This paper systematically compares the gas sensing properties of organic field‐effect transistors (OFETs) based on patterned 5,11‐bis(triethylsilylethynyl)anthradithiophene (TES‐ADT) films, by adopting TES‐ADT crystal arrays of various shapes and dimensions. The patterning and crystallization of spin‐cast TES‐ADT layers are achieved by the use of a solvent‐containing engraved polydimethylsiloxane (PDMS) mold. Decreasing width of the TES‐ADT pattern enhances gas sensing performance, as well as field‐effect mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Through the POM analysis, it was confirmed that the P3HT aggregates are accumulated at certain saturated levels in the 5 and 10 μm-width channels in ∼50 and ∼380 s, respectively, which is determined by comparing the time taken to reach a certain birefringent intensity (Figure 5). 34 Numerical Simulations of Diffusion Rate Depending on PDMS Channel Widths. In addition to the time sequential POM measurements following the solution diffusion, we conducted numerical simulations of P3HT molecule transport of each PDMS channel width condition (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Through the POM analysis, it was confirmed that the P3HT aggregates are accumulated at certain saturated levels in the 5 and 10 μm-width channels in ∼50 and ∼380 s, respectively, which is determined by comparing the time taken to reach a certain birefringent intensity (Figure 5). 34 Numerical Simulations of Diffusion Rate Depending on PDMS Channel Widths. In addition to the time sequential POM measurements following the solution diffusion, we conducted numerical simulations of P3HT molecule transport of each PDMS channel width condition (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the discovery of isomeric guest-host systems of TES ADT using blends of the two pure isomers provided further, detailed insight on the polymorph development of TES ADT. 51 Apart from high performance transistors, moreover, new applications of TES ADT are being explored, including gas sensors 52,53 and the use of this semiconducting small molecule in photon-upconversion. 54 These new research frontiers open new opportunities for TES ADT and other semiconducting small molecules and requires further insights into their solidification and controlled fabrication towards specific structures produced for targeted applications.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al systematically compared the gas sensing performances of NO 2 sensors on the basis of various types of patterned 5,11-bis(triethylsilylethynyl)anthradithiophene (TES-ADT) films. 60 Three types of TES-ADT crystal arrays were successfully achieved using engraved polydimethylsiloxane mold (Figure 7D,E). The type C device with decreased width of TES-ADT pattern displayed the highest NO 2 gas sensing property.…”
Section: No 2 Gas Sensorsmentioning
confidence: 99%